Early Iron Age – Medieval Period Settlement of Krasnoye-IV (Sannoye): to the question of the formation of the medieval population of Southern Zavolochye - Marina V. Ivanishcheva (Археология евразийских степей)
The article presents materials from the Krasnoye-IV (Sannoye) settlement, close to the Vanvizdino archaeological culture and earlier, studied by excavations supervised by the author in the middle parts of the Sukhona River in the Totma district of the Vologda region. The materials introduced into scientific discourse are of fundamental importance in the issue of the formation of the medieval population of the southern part of historical Zavolochye, on which the opinions of researchers differ. Researchers of medieval burial grounds known in this area since the beginning of the XX century believed that the burial monuments of the XII–XIII centuries in this area were left by the local population who were subjected to ancient Russian colonization. Another point of view assumes that the territory of Zavolochye was poorly populated before the arrival of the ancient Russian population, and the heterogeneous Finno-Ugric elements reflected in the burial sites were brought by people from various parts of Old Rus during fishing and hunting exploitation. Materials from the Krasnoye-IV (Sannoye) settlement demonstrate the habitation of the Finno-Permian population from the Glyadenovo period to the early Middle Ages. The article also gives a brief review of archaeological data on the region, demonstrating the significance of the East Finnic component throughout the entire era of the Early Iron Age and the Early Middle Ages in the Sukhona basin, the length of which is about 560 km, with only a few archaeologically studied monuments of this period.